we have

dv/dx = v-x^2+1 / x

then how do we deduce from that:

d(v/x)/dx = -1 + 1/x^2 ? ?

thanks

Printable View

- Apr 9th 2008, 10:22 AMRichyieHelp solving this diff equation please!
we have

dv/dx = v-x^2+1 / x

then how do we deduce from that:

d(v/x)/dx = -1 + 1/x^2 ? ?

thanks - Apr 9th 2008, 10:30 AMtopsquark
*Please*use parenthesis!!

$\displaystyle \frac{d}{dx} \left ( \frac{v}{x} \right ) = \frac{\frac{dv}{dx} x - v}{x^2}$

$\displaystyle = \frac{(v - x^2 + 1) - v}{x^2} = \frac{-x^2 + 1}{x^2} = -1 + \frac{1}{x^2}$

For the record:

v-x^2+1 / x is

$\displaystyle v - x^2 + \frac{1}{x}$

-Dan - Apr 9th 2008, 10:45 AMRichyie
yep i meant (v-x^2+1) / x sorry

thanks :)